On the Malware Detection Problem: Challenges & Novel Approaches - Botacin, Marcus; de Geus, Paulo; Grégio, André (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2022: Anais Estendidos do XXII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg_estendido.2022.224746, 2022)
Many solutions to detect malware have been proposed over time, but effective and efficient malware detection still remains an open problem. In this work, I take a look at some malware detection challenges and pitfalls to contribute towards increasing system’s malware detection capabilities. I propose a new approach to tackle malware research in a practical but still scientific manner and leverage this approach to investigate four issues: (i) the need for understanding context to allow proper detection of localized threats; (ii) the need for developing better metrics for AntiVirus (AV) evaluation; (iii) the feasibility of leveraging hardware-software collaboration for efficient AV implementation, and (iv) the need for predicting future threats to allow faster incident responses.